2014
DOI: 10.3766/jaaa.25.5.6
|View full text |Cite
|
Sign up to set email alerts
|

Wideband Absorbance in Young Infants (0–6 months): A Cross-Sectional Study

Abstract: Developmental effects of WBA were evident for infants during the first 6 mo of life. The WBA data can be used as a reference for detecting disorders in the sound-conductive pathways (outer and middle ear) in young infants. Further development of age-specific normative WBA data in young infants is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 31 publications
4
36
1
2
Order By: Relevance
“…Similar results have also been shown by international studies (14,(21)(22)(23)(24) , including one (25) reporting that the reflectance was greater at low frequencies (250 to 1000 Hz), decreased at medium frequencies (from 1000 Hz to 4000 Hz), and increased again above the frequency of 4000 Hz. Results obtained in a later study (26) , in turn.…”
Section: Discussionsupporting
confidence: 74%
“…Similar results have also been shown by international studies (14,(21)(22)(23)(24) , including one (25) reporting that the reflectance was greater at low frequencies (250 to 1000 Hz), decreased at medium frequencies (from 1000 Hz to 4000 Hz), and increased again above the frequency of 4000 Hz. Results obtained in a later study (26) , in turn.…”
Section: Discussionsupporting
confidence: 74%
“…There do not appear to be systematic differences between the newborn and 1-month-old response at other frequencies. (Keefe et al 1993;Sanford & Feeney 2008;Merchant et al 2010;Aithal et al 2014). Differences among the four datasets collected at birth might be explained by similar circumstances that were discussed above for the differences among the referred ears, as these data were from the same experimental conditions for the respective authors.…”
Section: Age Comparison: Changes In Power Reflectance Of Normal Ears mentioning
confidence: 93%
“…Right Power reflectance measurements made on newborn, 1-week, and 1-month-old ears that were assumed to have normal hearing at the time of measurement. Specifically, DPOAE screenings were passed for measurements made on ears by Aithal et al (2015Aithal et al ( , 2014, Hunter et al, Merchant et al (2010), Sanford et al, Sanford and Feeney (2008), and the present study. In addition, ABR measurements demonstrated normal hearing in the ears reported as normal by the present study and Aithal et al The data from "this study" shows the power reflectance from the same set of ears at birth and First, the conductive-loss assumption was confirmed for the data in the present study since the ear was tested again at age 1 month and determined to have normal hearing, whereas in the other three studies, the subjects simply referred on the DPOAE screening and it was never confirmed that the population consisted of only conductive-loss conditions.…”
Section: Association Of Ear's State On Power Reflectance Near Birthmentioning
confidence: 99%
“…A number of studies have shown [23,28,35] that the majority of the significant modification to the values of wideband absorbance occurs is the first 6 months of life, due to the development of the external and middle ear. During this period, there is an "absorbance immaturity" at low frequencies and an absorbance significant increase in the high frequencies.…”
Section: Immittance In Neonatesmentioning
confidence: 99%
“…Among the possible outcomes in neonatal hearing screening program, there are false positives that may result from differences in the development of ear structures that harm the impedance mechanism [23,28]. Due to the presence of amniotic fluid, meconium mesenchyme or the external auditory canal may cause temporary changes in hearing.…”
Section: Immittance In Neonatesmentioning
confidence: 99%